Effects of ozone therapy on surgically multi-treated retinal detachment. Case Report. (Ozone Therapy Global Journal, 2020)
Retinal detachment is the physical separation of the neurosensory retina from the retinal pigmented epithelium, developing vision loss. The surgical approach is recommended within the treatment, however, there are many adverse effects such as glaucoma, cataract formation, keratopathy, persistent tear eye, vitreous hemorrhages, among others. Therefore, the use of minimally invasive therapies with few adverse effects are of vital importance and it is known that the use of ozone therapy in ophthalmological diseases (macular degeneration, atrophy, retinal detachment), where a faster recovery of functions is observed, visual and decreased inflammatory processes. As observed in the clinical case we present, which after the diagnosis of retinal detachment and more than a year with multiple surgical treatments, it developed multiple adverse effects with considerable decrease in visual acuity and severe pain in the eye and skull. Where these persistent symptoms who lead him to a medical consultation at Wellness Weber ®, once we perform medical records, we starting treatment with systemic ozone therapy protocols and Ozonized Growth Factors (FCC O3). At the end of the ozonetherapy treatment there was an improvement in the visual capacity, as well as an important improvement of peripheral vision and visual capacity almost in its entirety, an increase in refraction to light and healthy macula in its entirety. This could be explained thanks to the effects of ozone therapy at the ocular level, such as decreased proinflammatory substances, antiseptic capacity, increased antioxidant enzymes, improving the functional activity of neurons in the macular area, partially restoring corriorretinal blood flow, decreasing hypoxia and ischemia, leading to a shorter healing time an increase in visual acuity and visual field for this reason we propose ozone therapy as adjuvant therapy in retinal detachment.